RANCANG BANGUN ELECTROCARDIOGRAF PENDETEKSI LEFT VENTRICULAR FAILURE - Dea Africo Santoso; Youlanda Fahmyantoro; Sulfan Bagus Setyawan (PROSIDING SNAST, 2018)
trocardiogram (ECG) is a medical test to detect heart abnormalities by measuring the electrical activity produced by the heart, as the heart contracts. ECG can help diagnose various health conditions such as cardiac arrhythmias, heart enlargement, heart inflammation (pericarditis or myocarditis), and coronary heart disease. In general, detection of heart disease can only be done in a hospital using ECG. The system that is used now also cannot be used to automatically detect the patient's illness when using the ECG. In this paper the author makes a tool that can detect portable heart signals. From the detected heart signal we can determine that the heart's condition is normal or there is an abnormality in the heart. The heart signal was detected from the electrode clamp sensor mounted on the right arm (RA), left arm (LA) and right leg (RL). The signal from the sensor is amplified with an amplifier amplifier circuit so that it can be read by the STM32F4 ARM microcontroller. The microcontroller processes the signal from the sensor and will be displayed on the Computer Application. Connection between Microcontroller and PC using a Bluetooth serial connection. The final appearance in this final project can display the shape of the ECG signal and determine that the heart is normal or abnormal. Based on the test results obtained from the comparison of ECG devices made with the ECG type BTL-08 SD there is an error of 1.06%.